Sosialisasi Pembuatan Kertas Dari Limbah Daun Serai Wangi - Adisyahputra, Adisyahputra (Fakultas Teknik, Universitas Bangka Belitung, 2023)
Distilling citronella produces quite a large amount of citronella leaf waste. Each harvest season produces around two tons of wet citronella leaves which are then distilled to produce essential oil, leaving behind waste. Based on this, service was carried out in Jada Bahrin Village through outreach in processing citronella leaf waste into paper. It is hoped that this service can support the priority development of the 2017-2045 National Research Master Plan which focuses on the food-agriculture sector while still referring to the Bangka Belitung University Community Service Strategic Plan for 2021-2025.